Shaping gels and gels mixture to create helices - D'angelo, María Verónica (2022)
In cooking, food gels, such as agar-agar or alginate, are often prepared and presented in the form of spheres or spaghetti. While experimenting in our kitchen, we realized that it is quite difficult to make more advanced shapes. In this study, we sought to develop new methods to obtain more complex shapes. Our first challenge was to obtain helices. The best method we selected was to deposit the solutions before their gelation in a thread. The robustness of the method is tested by systematically changing the thread pitch, diameter, and depth. From the deformation under its own weight, we propose to deduce the mechanical characteristics of the helix. These values are compared to those obtained in the laboratory using indentation testing. Finally, we experimented with mixed gels obtained by combining agar-agar and alginate.